Implementing the Monday-Thursday Voluntary Fasting Program to Strengthen Students’ Religious Commitment at Asy-Syifa Modern Islamic Boarding School, Balikpapan - Fahreza, Rasya; Sa’dullah, Sa’dullah (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
Islamic boarding schools have been known as educational institutions that are effective in shaping the level of religiosity of their students through various religious activities scheduled as a routine, by consistently instilling religious values in the students. Islamic boarding schools hope that every student not only has a good understanding and knowledge of religious values, but is also able to practice these teachings in everyday life. Religiosity can be defined as a deep appreciation of the values of religious teachings that have been internalized within individuals, which are then realized through their daily actions and behavior. Pondok Modern Asy-Asyifa Balikpapan is an Islamic boarding school that has implemented a Monday and Thursday fasting program. Where we know that Islamic boarding schools are a place for students to improve and develop religious values. The implementation of the Monday and Thursday fasting program carried out by Pondok Modern Asy-Syifa Balikpapan in increasing the religiosity of students, including getting closer to Allah and carrying out the Sunnah of the Prophet, Monday and Thursday fasting also trains patience, sincerity and istiqomah in carrying out worship, apart from that it can also form attitudes. discipline, maintaining health and maintaining solidarity between students.